2012
DOI: 10.1038/gim.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the inputs, analyses, and outputs of biobank research systems to identify sources of incidental findings and individual research results for potential return to participants

Abstract: Progress in the debate over returning incidental findings (IFs) and individual research results (IRRs) to research participants who provide specimens and data to biobanks in genetic and genomic research requires a new tool to allow comparison across heterogeneous biobank research systems and in-depth analysis of the sources and types of findings generated for potential return. This paper presents a new visual mapping tool to allow systematic and standardized depiction of (1) the specimens initially collected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For example, professional organizations 4 and government initiatives 5 are important resources. Nevertheless, there is extensive variation among biobanks with respect to initial motivation to create the biobank, settings of biobanks (e.g., academic, clinical, or commercial), data and biospecimen inventories, 6 data management and security, scope (e.g., single institution samples versus regional or national sample contributions), and sharing policies. As a result of the diverse motivations and goals, context matters.…”
Section: Surveys Of Biobank Managers’ Views On Return Of Resultsmentioning
confidence: 99%
“…For example, professional organizations 4 and government initiatives 5 are important resources. Nevertheless, there is extensive variation among biobanks with respect to initial motivation to create the biobank, settings of biobanks (e.g., academic, clinical, or commercial), data and biospecimen inventories, 6 data management and security, scope (e.g., single institution samples versus regional or national sample contributions), and sharing policies. As a result of the diverse motivations and goals, context matters.…”
Section: Surveys Of Biobank Managers’ Views On Return Of Resultsmentioning
confidence: 99%
“…Fully engaging researchers in deliberative processes to develop strategies to respond to ethical issues in their human subject research may also prove to benefi t the process of research design generally. Further, as new technologies, such as next generation sequencing become more common, complicated issues about how to respond to incidental fi ndings will more common, 11 and REC services may be well positioned to provide advice and guidance. 12 Th ese collaborative eff orts may be increasingly important as emerging informatics capabilities, the rapid pace of technology development, and greater involvement of communities in the research process have made the ethical issues in clinical and translational research more visible and perhaps even more complicated than previously.…”
Section: Discussionmentioning
confidence: 99%
“…Most services reported that several areas of expertise were represented on their RECS. Backgrounds of RECS consultants included bioethics (31), medicine (26), humanities (19), law (14), epidemiology/public health (11), biological sciences (9), and social sciences (9).…”
Section: Consultant Staffi Ngmentioning
confidence: 99%
“…First, ''financial and logistical complications'' (Samuel et al, 2012) can be minimized, thanks to scientific advances. Technical solutions exist, for example, tools to compare and manage results and the process of returning them to participants' treating physicians (Bemmels et al, 2012).…”
Section: In Favor Of a Pragmatic And Honest Solutionmentioning
confidence: 99%